Programa para la producción de moluscos en Venezuela - Antunes, S.A. (1978)
This paper discusses an integrated project in Venezuela, planned and designed lo ascertain the best procedures required for production of large quantilies of shellfish, including: selection and maintenance of pollution-free growing areas; the best harvesting methods; and the safest and most economical marketing procedures. The major problems involved in producing safe, wholesome and nutritious shellfish are primarily those of sanitation and adequate preservation of the foods until they finally reach the consumer. Therefore, it is essential that these products be produced and handled in a sanitary manner on a continuous basis. There are numerous codes of recommended handling practices for shellfish, most developed only after many technical conferences were organized to evaluate all of the available scientific evidence. Therefore, for producing safe shellfish in Venezuela, this publication recommends the adoption of there sanitary and handling practices, designed and tested by the faculty and staff personnel of Universidad Simón Bolívar.